AgreementTech: Innovation of Employment Agreements Based on Digital Leadership in the Era of Disruption in West Sumatra - Fikrina, Aulia; Sarianti, Kiki; Sucia, Yossiramah (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
This study aims to analyze the innovation of AgreementTech in employment agreements based on digital leadership in the disruption era, with a specific focus on the socio-cultural and legal context of West Sumatra. Digital transformation has reshaped employment relations through the emergence of electronic contracts and technology-based systems, yet legal certainty and organizational readiness remain major challenges. A mixed-methods approach with a sequential explanatory design was employed, in which quantitative data were collected through surveys of employees and company managers, followed by qualitative data obtained through in-depth interviews with company leaders, HR practitioners, and labor law experts. The findings reveal that the Disruption Era significantly influences employment contract innovation through AgreementTech, while the direct effect of digital leadership is not significant. Nevertheless, digital leadership strongly influences organizational readiness to face the disruption era, thereby indirectly encouraging the adoption of AgreementTech. From a legal perspective, the study highlights the need for a reconstruction of contract law norms to accommodate electronic agreements, including stronger regulation of digital signatures and the evidentiary status of digital contracts in court. Accordingly, the combination of external pressures, digital leadership, and the renewal of contract law constitutes the foundation for the implementation of AgreementTech in the digital era.